Studi Tematik Hadis Toxic Friendship dengan Pendekatan Akhlak - Ro’sa Romdhonah; Mus’idul Millah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study is to discuss the hadith views about toxic friendship in a hadith perspective throught thematic methods. In research using qualitative research types and applying thematic methods, namely tracing the hadiths about friendship. The results of this study show that not everything goes well in a relationship. The term toxic friendship is used to describe an unhealthy friendship. The relationship that is going through is clearly toxic which can be harmful and even destroy happiness. Toxic friendship often appears in several friendships, and often a person cannot get out of such a state. This triggers the emergence of curiosity about the views of the hadith regarding toxic friendship. By doing so, the writer can draw the conclusion that this paper can be a reference for teenagers to be selective in choosing an ideal friend.